New Approaches to Studying Prevalence Gallstone Disease - N. A. Khokhlacheva; T. S. Kosareva; A. P. Lukashevich (SINAPS LLC, 2020)
The aim - predicting the growth of gallstone disease based on the study of the dynamics of the incidence of the liver. Materials and methods. In clinical conditions, 98 patients (62 women and 36 men, average age 43.4 ± 3.3 years (21-60)) with various chronic liver diseases were examined. Anamnesis, clinical and laboratory data were used to verify the diagnosis. In portions "B" and "C" of bile obtained by multifractional duodenal sounding, the total concentration of bile acids, cholesterol and phospholipids was determined, and lithogenicity indices of bile were calculated: cholate-cholesterol and phospholipid-cholesterol coefficients. The results were analyzed using Microsoft Excel 2010 and PSPP statistical processing programs. The next stage of the work was the analysis of statistical indicators of the general and primary liver morbidity in the Udmurt Republic over the past 10 years (2008-2018). The study applied statistical forecasting methods. Models were built in the Microsoft Excel 2010 program in a polynomial trend.Results. In 52 (53,1%) examined patients, ultrasound examination of the gallbladder were signs of biliary sludge. Microscopic examination of bile 71 (72,6%) patients had crystals of cholesterol and calcium bilirubinate, which is evidence of stage I gallstone disease. In all patients with biliary sludge, a violation of the biochemical composition of bile was noted - a decrease in the concentration of bile acids and phospholipids, an increase in the concentration of cholesterol, a decrease in cholesterol and phospholipid-cholesterol coefficients. When studying statistical indicators over the past 10 years, a higher general and primary incidence of liver diseases in the Udmurt Republic was noted than in the Russian Federation as a whole. Based on the results of trend modeling, a significant increase in the total and primary liver morbidity is predicted both in the Udmurt Republic and in the Russian Federation.Conclusion. Summarizing the data obtained, it can be noted that over the past 10 years (from 2008 to 2018) among the adult population of Udmurt Republic, a clear tendency has been revealed for an increase in the general and primary incidence of the liver. As the results of trend forecasting showed, an increase in the incidence of the liver will continue in the coming years. With liver pathology, bile secretory function suffers, as a result of metabolic processes, bile produces supersaturated cholesterol, which is the basis for stone formation in the gall bladder. A study of the dynamics of liver disease allows predicting an increase in cholelithiasis in the coming years. Despite the fact that the asymptomatic course of cholelithiasis is often quite observed, if this disease is not diagnosed and the preventive treatment of stone formation is not carried out in a timely manner, this leads to the development of serious complications.